Fourfold amplification of solitary-wave Mach reflection at a vertical wall. (3rd January 2019) - Knowles, Jeffrey; Yeh, Harry
Abstract : With the use of a higher-order Euler formulation, we numerically study the reflection of an obliquely incident solitary wave at a vertical wall and compare results with the higher-order Kadomtsev–Petviashvili theory. A maximum amplification of 3.91 is achieved along the wall, nearly realizing the fourfold prediction by Miles ( J. Fluid Mech., vol. 79 (1), 1977, pp. 171–179).